Organizational climate and perceived manager effectiveness : influencing perceived usefulness of knowledge sharing mechanisms - Boh, Wai Fong (2013)
In this study, we examine how perceptions of organizational climate and manager effectiveness influence individuals’ perceived usefulness of three types of knowledge sharing mechanisms (KSMs): (1) informal personalization KSMs, (2) formal codification KSMs, and (3) formal personalization KSMs. We collected survey data from 1036 employees from five different subsidiaries of an organization to test our hypotheses. We found that having a warm and cooperative climate has a positive influence on individuals’ perceptions of all KSMs. A competitive climate, on the other hand, increases individuals’ preference for using formal codification and personalization mechanisms relative to informal personalization mechanisms. Finally, individuals who perceive their managers to be more effective tend to be more supportive of top-down initiatives provided by senior management; thus, these individuals have a significantly more positive opinion of formal mechanisms compared to informal mechanisms. This study provides an extended and more nuanced perspective of how knowledge sharing can be enabled in different social contexts. The results will help managers to customize a portfolio of knowledge management mechanisms based on the climate of their organizational unit.